Estimation of dental age using the Kvaal method with digital panoramic radiographs in peruvian adults = Estimación de la edad dental según el método de Kvaal con radiografías panorámicas digitales en adultos peruanos - Izaguirre López, Heikky N.
To determine the accuracy of the Kvaal method in the estimation of dental age through the analysis of digital panoramic radiographs of patients between 20 and 47 years of age who attended the stomatological clinic of the Universidad Científica del Sur, (2018 to 2019), Lima-Perú. 289 digital panoramic radiographs belonging to individuals of both sexes, aged 20 to 47 years were analyzed. Length and width measurements were obtained in the dental and pulp chamber in the upper central incisors. These data were subsequently evaluated by calculating the proportions between the pulp and root length of the upper central incisor by applying the formula of the method of Kvaal et al. to obtain the accuracy of the method in estimating dental age. Applying the formula of Kvaal et al. indicates that the relationship between the width of the pulp and the length of the root has a higher level of significance in relation to others proportions: M mean value of all ratios except T (-0.659) and W-L difference between W and L (-0.643). The coefficient of determination (r²) and standard error of estimation (SEE) using the original Kvaal formula is r²: 0.70, SEE: 4.90 years, then a modified Kvaal formula was proposed for the Peruvian population. The Method of Kvaal et al. has an accuracy of 1.24 in estimating the dental age of individuals, using the upper central incisor in digital panoramic radiographs.